2017
DOI: 10.1186/s12889-016-3917-9
|View full text |Cite
|
Sign up to set email alerts
|

An objective and cross-sectional examination of sun-safe behaviours in New South Wales primary schools

Abstract: BackgroundPrevious evaluations have supported the link between sun protection policies and improved sun protection behaviours. However these evaluations have relied on self-reported data.MethodsA cross-sectional design as part of an ongoing 18-month cluster-controlled trial in primary schools (n = 20) was used. Researchers conducted direct observations to record students’ hat use and teachers’ use of sun protective measures during recess and lunch. Researchers also recorded the volume of sunscreen consumed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 13 publications
(17 reference statements)
0
18
1
Order By: Relevance
“…While Sharplin and Roth 12 found that NSW primary schools were 20% more likely to make sunscreen available at special occasions, i.e. sport excursions, than in all classrooms, the findings of this study and Dudley et al 18 indicate that sunscreen consumption in NSW SunSmart schools is minimal. These findings suggest that while triggers activate an intention to engage in sun protection behaviours, the basic provision of resources is not sufficient in facilitating sun protection behaviours for all individuals.…”
Section: Discussioncontrasting
confidence: 74%
See 4 more Smart Citations
“…While Sharplin and Roth 12 found that NSW primary schools were 20% more likely to make sunscreen available at special occasions, i.e. sport excursions, than in all classrooms, the findings of this study and Dudley et al 18 indicate that sunscreen consumption in NSW SunSmart schools is minimal. These findings suggest that while triggers activate an intention to engage in sun protection behaviours, the basic provision of resources is not sufficient in facilitating sun protection behaviours for all individuals.…”
Section: Discussioncontrasting
confidence: 74%
“…This finding aligns with previous research highlighting the strong link between sun protection policy and hat-wearing requirements, specifically students relocating to a shaded area if a school-assigned hat wasn't worn. 13,14,16,17 However, reviews of the SSP using objective measurements have found that hat-wearing behaviour in SunSmart schools is far less than had been self-reported in other studies 18 and was comparable to schools without a SunSmart membership. 19 The findings of this research identify a number of factors that may be influencing the division between hat-wearing policy and practice.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations